A tighter upper bound on the Lebesgue constant of Berrut's rational interpolant at equidistant nodes. (September 2016) - Deng, Chongyang; Zhang, Shankui; Li, Yajuan; Jin, Wenbiao; Zhao, Yi
Abstract: The Lebesgue constant of interpolation operators plays an important role in approximation theory. Several upper bounds have been achieved on the Lebesgue constant of Berrut's rational interpolation operator. The aim of this paper is to investigate the Lebesgue constant of Berrut's rational interpolant at equidistant nodes, and present a tight upper bound.